Website Design for Solving and Securing Confidential Files with the Asmuth Bloom Secret Sharing Protocol - Fernando, Edward; Edi; Pribadi, Octara (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Conventional cryptographic algorithms cannot be applied to break a plaintext (message) into several ciphertexts because conventional cryptographic algorithms can only produce one ciphertext from a plaintext (message). In this case, a cryptographic protocol can be applied, namely the Asmuth-Bloom secret sharing protocol. The working process of the Asmuth-Bloom secret sharing protocol is divided into two parts, namely the shadow formation process and the shadow merging process. The shadow formation process will start from the process of filling in the message and the collection of d values ​​along with the values ​​​​of m, n and prime numbers p. After that, the process is continued by converting the message to ASCII Code. After that, each value will be processed according to the input d value so that a collection of shares is obtained. Meanwhile, the shadow merging process will start from filling in m shares. After that, the process is continued with the calculation of each character using the Chinese Remainder Theorem. The process will end with the merging of each character produced so that the original message is obtained. The results of this study are in the form of a website-based application that provides an interface to carry out the process of breaking text files into n shadow files and merging m shadow files into the original text file.